Volume 3: Structures, Safety, and Reliability 2018
DOI: 10.1115/omae2018-77552
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial Fatigue Analysis of Mooring Chain Links Under Tension Loading: Influence of Mean Load and Simplified Assessment

Abstract: Current standards (as an example, DNV-OS-E301[1] and API-RP-2SK[2]) do not account for mean load in the fatigue assessment of mooring chains. Both standards, provide S-N curves derived from experimental work without specifying the mean load for which they have been obtained or proposing a mean load correction function. This paper reports a fatigue analysis study of mooring chains under Tension Loading using a multiaxial fatigue criterion for two different mean loads. Multiaxial fatigue criteria enable to accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
(198 reference statements)
1
1
0
Order By: Relevance
“…One chain section was however tested at a mean load of 10% MBL, and obtained a fatigue life that was significantly longer than the chains that were tested with the same stress range but at the higher mean load. A similar case was studied numerically by Martinez Perez et al [11], and it was confirmed that a reduced mean load had a positive effect on the fatigue life of the mooring link considered.…”
Section: Effect Of Mean Loadsupporting
confidence: 61%
“…One chain section was however tested at a mean load of 10% MBL, and obtained a fatigue life that was significantly longer than the chains that were tested with the same stress range but at the higher mean load. A similar case was studied numerically by Martinez Perez et al [11], and it was confirmed that a reduced mean load had a positive effect on the fatigue life of the mooring link considered.…”
Section: Effect Of Mean Loadsupporting
confidence: 61%
“…The effects of mean load and corrosion on fatigue of mooring chain have been addressed previously. Martinez Perez et al (2018 presented a computational method that accounts for the influence of mean load on the fatigue lifetime of new mooring chain. Zarandi and Skallerud (2020) investigated the effect of mean load including residual stresses on the fatigue crack initiation of corroded chains using experiments and finite element analysis.…”
Section: Introductionmentioning
confidence: 99%